Neoclerodane and labdane diterpenoids from Plectranthus ornatus - Rijo, P (2015)
Three new diterpenoids, a neoclerodane and two labdane derivatives, have been isolated from an acetone extract of Plectranthus ornatus. The structures. of these compounds (plectrornatins A-C, 1-3, respectively) were established mainly by spectroscopic means, particularly by 1D and 2D NMR studies and, in the case of the neoclerodane 1, by an X-ray diffraction analysis. Compounds. 1 and 3 showed moderate antimicrobial against five Candida species and selected Gram negative and Gram positive bacteria strains.